2014
DOI: 10.1590/0004-2730000003456
|View full text |Cite
|
Sign up to set email alerts
|

Trabecular bone score: perspectives of an imaging technology coming of age

Abstract: The trabecular bone score (TBS) is a new method to describe skeletal microarchitecture from the dual energy X-ray absorptiometry (DXA) image of the lumbar spine. While TBS is not a direct physical measurement of trabecular microarchitecture, it correlates with micro-computed tomography (µCT) measures of bone volume fraction, connectivity density, trabecular number, and trabecular separation, and with vertebral mechanical behavior in ex vivo studies. In human subjects, TBS has been shown to be associated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 50 publications
2
38
1
7
Order By: Relevance
“…The precision of the measurement is critical, both within and between instruments [64]. However, sensitivity to measure changes is also affected by responsiveness, the ratio of responsiveness to precision being an indicator of sensitivity to measure (treatment-induced) changes [65].…”
Section: Is Tbs Responsive To Treatment?mentioning
confidence: 99%
“…The precision of the measurement is critical, both within and between instruments [64]. However, sensitivity to measure changes is also affected by responsiveness, the ratio of responsiveness to precision being an indicator of sensitivity to measure (treatment-induced) changes [65].…”
Section: Is Tbs Responsive To Treatment?mentioning
confidence: 99%
“…Low TBS values are related to altered bone microarchitecture and increased risk of fragility fractures, independent of BMD [18]. An international working group of TBS users has proposed TBS cut-off values for postmenopausal women: normal for TBS values over 1.350, partly degraded microarchitecture for values between 1.200 and 1.350, and degraded for values 1.200 or less [19] (http://www. medimapsgroup.com/upload/MEDIMAPS-UK-WEB.pdf).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the hydrogimnastic training program in these research was designed five times a week whit periodization in order to produce grater adaptations (23), increasing the load heart rate reserve of 40-50% (1-6 th week) increasing the load to 50-60% heart rate reserve (7)(8)(9)(10)(11)(12) th week) these result was not consistent with a controlled trial than evaluate with biochemical markers of bone turnover in elderly who practice aquatic exercise than showed serum osteocalcin, intra and intergroup statistical differences of p = 0.042 and p = 0.027 (22), other study than showed benefits in bone formation marker assessed by procollagen type 1 amino-terminal propeptide (15.8 %; p = 0.001) after a high-intensity of aquatic exercise program in postmenopausal women (27); these discrepancies with our results may be owing to de time than were performed through 24 weeks of aquatic exercises but with lower frequency (3 times a week) and lower work load intensity by other hand some of these programs where attendance in strength modalities in to the water than may have influence the improvements in bone turnover (9,27).…”
Section: Discussionmentioning
confidence: 99%
“…Controlled trials in post-menopausal women have been considered physical exercise along with medication and diet one of the three cornerstones of osteoporosis (10,11). By other hand, there are different accepted diagnostic criteria to identify osteoporosis than may partly explain the variability of prevalence (12); also the incidence of physical exercise to induce changes in bone metabolism is determined for the duration, intensity and type of exercises (9).…”
Section: Introductionmentioning
confidence: 99%